Leveraging the Power of Servant Leadership Building High Performing Organizations - Laub, James (Palgrave Studies in Workplace Spirituality and Fulfillment,, 2018)
This book provides a consistent model to understand leadership as a dynamic combination of vision, action, mobilization, and change. It puts servant leadership into a historical and theoretical context while providing a research-based approach and conceptual model that deepens our understanding of the topic. Further, it provides ways to implement this approach to leadership in real organizational settings. The goal is to bridge the gap between scholarly research and the practical realities of leadership within organizations, communities, and society at large. The author presents the Organizational Leadership Assessment (OLA) and model with research support which will guide students and leaders in evaluating organizational health and effectiveness. .